Building a High-Performing Collaborative Innovation Ecosystem in the Arctic - Sofroneeva, Ekaterina; von Koskull, Catharina; Makkonen, Hannu (Arctic Portal, 2021)
Global climate change, growing economic interest in the Arctic, and the inflow of investments into infrastructure in the Arctic regions have provided added impetus for the development of technology clusters and innovation ecosystems in the North and the Arctic. The goal of this study is to conceptually illustrate the roles of the actors involved in the development process of the innovation ecosystem in the Arctic regions. This research is crucial for optimizing the role of the actors responsible for the genesis of the innovation ecosystem in the Arctic regions and is based on a case study of the Yakutia innovation ecosystem. The Republic of Sakha (Yakutia) currently holds the leading position in the IT sphere of Far East Russia, accounting for 85% of the region’s IT services exports in the first quarter of 2020 and 82% in 2019. Yakutia develops the northernmost innovation ecosystem, with IT Park Yakutsk as its base, in collaboration with different actors from governments, universities, startup communities, and venture capital firms. This study applies a qualitative approach, with the data collection conducted using in-depth interviews. The interviewees in this study represent various actors, including businesses, governments, universities, and financial institutions. Theories developed by Dedehayir et al. (2018) and Tsujimoto et al. (2018) are used to explain and analyze the disposition, roles, and interactions of the actors during the genesis (birth phase) of the innovation ecosystem in the North. This study argues that building high-performing innovation ecosystems will produce digital and economic transformations that improve the sustainability and resilience of the societies in the Arctic.
Keywords: fi=Markkinointi|en=Marketing|